Risk Adjustment of Capitation Payment System: What Can Indonesia Adopt from other Countries? - Zahroh, Asri Hikmatuz (UI Scholars Hub, 2018)
Capitation calculation in Indonesia is not adjusted by individual and aggregate risk. Without risk adjustment, capitation rates are likely to overpay or underpay primary care. This study aimed to review risk-adjusted capitation payment in other countries for evaluation of capitation payment system in Indonesia. The conduct and reporting of this systematic review followed the recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). This study used comprehensive electronic search in five databases: Pubmed, Proquest, Scopus, PMC, and EBSCOHost. Search results from five databases in April 2018, yielded a total 19 titles that will continue to review the full article and at the end, 4 articles included for systematic review. Based on risk adjustment of capitation payment system in UK, USA, Canada and Sweden, Indonesia may initiate the use of risk adjustment based on the distribution of age and sex. Then Indonesia can develop risk adjustment based on diagnosis and socioeconomic factors to create more fair and accurate capitation rates for primary care.